From monumentality to diversity – Lourenço Marques between the urban plans of Aguiar and Azevedo (1950-1970) - Pinto, P. T.; Milheiro, A. V.; Miranda, E.; Pinto, P. (Planning Perspectives, 2022)
The General Urban Development Plan for Lourenço Marques (today Maputo) was approved on 25th April 1955. Coordinated by architect João Aguiar, director of the Colonial Planning Office. it was developed based on the first urban plan for the city, which had been drawn up by Joaquim José Machado and António José de Araújo in 1887. A further new Master Plan for Lourenço Marques was drawn up between 1967 and 1969. This new one was the last before Mozambique gained independence in 1975 and it was drafted by a specialist team coordinated by the engineer and urbanist Mário de Azevedo. The orientations applied in Aguiar’s Urban Plan were quite distinct from those of Azevedo's Master Plan. The innovative element was that it opposed the ‘conception of a city closed in on itself, limited in size and structure’. Azevedo's plan furthered a regional interpretation of the territory and placed the emphasis on the provision of an entire transport infrastructure network by land, sea, and air. This paper seeks to throw light on the evolution of Portuguese urbanism in the Portuguese African colonies in the last years of colonization with a view to highlighting the different approaches.